A MoS2 / layered silicate nanocomposite catalyst and its preparation and application

By combining with layered silicate nanomaterials, MoS2/layered silicate nanocomposite catalyst was prepared, which solved the problem of insufficient exposure of the catalyst active site, and achieved efficient hydrogenation of heavy oil and catalyst stability sex.

CN116273068BActive Publication Date: 2025-02-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111521910.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-13
Publication Date
2025-02-14
Estimated Expiration
2041-12-13

AI Technical Summary

Technical Problem

The existing MoS2 catalysts have insufficient exposure to the active site during the hydrogenation process of heavy oil suspension beds and cannot fully contact with asphaltene, resulting in low reaction efficiency, easy deactivation of the catalyst and easy clogging of the reactor.

Method used

By composited with layered silicate nanomaterials, MoS2/layered silicate nanocomposite catalyst was prepared, and high-speed shear emulsification and mechanical stirring were used to ensure that the MoS2 nanosheets were on the surface island of the layered silicate single-layer disk. , and the catalytic active sites are exposed to the maximum extent.

Benefits of technology

High dispersion of the catalyst and abundant active site exposure are achieved, the conversion and yield of hydrogenation of heavy oils is improved, and catalyst deactivation and reactor clogging are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003407995370000091
    Figure BDA0003407995370000091
  • Figure HDA0003407995380000011
    Figure HDA0003407995380000011
  • Figure HDA0003407995380000012
    Figure HDA0003407995380000012
Patent Text Reader

Abstract

The invention relates to a heavy oil hydrogenation lightening catalyst development technology in the field of industrial catalysis technology, and is a MoS2 / layered silicate nanocomposite catalyst and its preparation and application. The nanocomposite catalyst comprises a MoS2 nanosheet and a layered silicate monolayer disc, and is a MoS2 / layered silicate nanocomposite catalyst formed by island-shaped distribution of non-agglomerated single MoS2 nanosheets on the surface of the monolayered nanolayered silicate disc. The MoS2 / layered silicate nanocomposite catalyst obtained by the invention can be used for hydrogenation of heavy oil suspension phase with API less than 20 to produce light oil products, and the layered MoS2 active component is island-shaped on the layered silicate surface, fully exposing its catalytic hydrogenation activity, and can be inserted into the condensed aromatic nucleus of the asphaltene component that is difficult to hydrogenate in the heavy oil, thereby quickly realizing its rapid hydrogenation conversion and avoiding the deactivation of the catalyst caused by asphaltene coking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to a MoS2 / layered silicate nanocomposite catalyst and its preparation and application, in particular to improving the effect of active sites of the catalyst on asphaltene, and belongs to the catalyst development technology in the field of industrial catalysis technology. Background technology:

[0002] Transition metal sulfide MoS2 has a typical layered structure, with weaker van der Waals forces between layers, easy to peel off, and an interlayer spacing of about 0.62nm. Each molybdenum atom in a single atomic layer is surrounded by six sulfur atoms, forming a triangular prism, exposing many Mo-S facets, which can be used as catalytic active centers. (See Chianelli, RR Catal. Rev. 2006, 48 (1), 1-41) Because MoS2 has special layered structure, anisotropy, electronic properties and precious metal-like properties, current research on this material is mainly focused on catalytic hydrogenation, electrocatalysis, electrode materials, photocatalysis, friction lubrication, electronic probes, hydrogen storage materials and many other fields. MoS2 has become a hot material in the fields of chemistry, physics, and materials science at home and abroad.

[0003] As people's interest in layered MoS2 materials increases, and because of its high hydrogenation activity and good anti-poisoning ability, it is widely used as a catalyst in the oil refining industry, such as oil hydrogenation and upgrading, including hydrogenation reactions, hydrodesulfurization, hydrodeoxygenation, and hydrodenitrogenation reactions. (See Prins, R. et al. Catal. Today 2006, 111 (1–2), 84-93) The catalytic hydrogenation activity of MoS2 materials is closely related to its structural characteristics. Since the catalytic hydrogenation active centers of MoS2 are mainly located on the edge faces, the surface energy is relatively high, which is 0.7 J / m 2 The surface is active and unstable, providing active centers for heterogeneous catalytic hydrogenation reactions. By developing catalyst preparation technology, the exposure of MoS2 hydrogenation active edges is increased, thus obtaining a highly active hydrogenation catalyst.

[0004] The suspended bed hydrogenation process is an advanced technology for hydrogenating heavy oil to produce liquid fuel oil. Heavy oil is oil with a crude oil API gravity of less than 20, API = 141.5 / crude oil density - 131.5. The suspended bed hydrogenation process requires the catalyst to have high activity, high dispersibility, high stability, and good economy. The preparation of catalysts suitable for the suspended bed hydrogenation process is a challenging topic. At present, the most active suspended bed hydrogenation catalyst is the MoS2-based catalyst.

[0005] So far, there are many methods for preparing nano-MoS2, and the morphology of the products is also various. CN103086436 discloses a method for preparing flower-shaped and rod-shaped nano-MoS2 in a reaction system, in which inorganic salts need to be added for auxiliary regulation to prepare flower-shaped and rod-shaped nano-MoS2. CN201410436988.6 discloses a method for hydrothermally synthesizing uniform MoS2 nano-flower balls using citric acid as a complexing agent. CN2015108639802 discloses a method for hydrothermally synthesizing polyhedral hollow MoS2 particles assisted by ionic liquids. CN201410758657.4 discloses a method for preparing MoS2 microspheres in a reverse microemulsion system. The above-mentioned wet chemical synthesis of MoS2 materials has nanosheets stacked and assembled to a size of several hundred nanometers or even micrometers, and the large number of nanosheet stacking layers is not conducive to the exposure of its active sites. However, due to the high surface energy of the MoS2 nanosheet produced in the wet synthesis process, it is aggregated into micro / nanospheres, nanoflowers, hollow cages and other morphologies to reduce the surface energy during the crystallization process, which undoubtedly causes many catalytic active sites to be embedded and covered. In addition, the dispersibility and suspension degree of this self-agglomerated MoS2 material in the heavy oil suspended bed hydrogenation system need to be improved. An improved method for the above-mentioned problems is to prepare a composite material of MoS2 and nanocarriers. The highly active MoS2 catalyst is prepared by using a highly dispersed nanocarrier loaded monolayer few-layer MoS2 nanosheet, which can both expose the active sites to the greatest extent and ensure the high dispersibility of the catalyst in the suspended bed hydrogenation system reaction.

[0006] Layered silicates are all in the form of pseudo-hexagonal sheets or short columns, with complete {001} dissociation. In terms of physical and chemical properties, they are characterized by low hardness, low density, high dispersibility, large specific surface area, special layered structure and nano effect. Among their many properties, the most striking are their catalytic performance, swelling (or expansibility), exchangeability of ion adsorption, plasticity and other special functions. These properties are widely used in the fields of materials science, petroleum, engineering geology, environmental protection, etc. Layered silicates are abundant in resources, cheap and easy to obtain, and have a unique layered structure and good ion exchange performance. Therefore, they are expected to be compounded with MoS2 catalysts, which also have a layered structure, to prepare MoS2 / layered silicate nanocomposite catalysts with high dispersion and high active site exposure. Summary of the invention:

[0007] The present invention provides a MoS2 / layered silicate nanocomposite catalyst and its preparation and application. The catalyst structure is innovated by developing a preparation method, overcoming the deficiencies of the above-mentioned prior art. The catalyst can effectively solve the problem of low exposure of catalyst active sites and failure to fully contact with asphaltene and react quickly in the process of hydrogenating heavy oil with an API value of 1 to 20 to produce light oil products, thereby achieving full conversion of asphaltene without coking and avoiding the problems of catalyst deactivation and reactor blockage.

[0008] The technical solution of the present invention is achieved by the following measures:

[0009] A MoS2 / layered silicate nanocomposite catalyst, the structural features of which mainly include that the nanocomposite catalyst includes MoS2 nanosheets and layered silicate monolayer discs, and the structure is a MoS2 / layered silicate nanocomposite catalyst formed by island-shaped distribution of non-agglomerated single MoS2 nanosheets on the surface of the monolayered nanolayered silicate disc. The thickness of the single MoS2 nanosheet is 0.6-3.0nm, and the length of the farthest two points on the side of the sheet is not more than 10nm; the diameter of the nanolayered silicate monolayer disc is 20-30nm, and the thickness is 0.2-1.7nm.

[0010] The preparation method of the MoS2 / layered silicate nanocomposite catalyst of the above structure is obtained by the following steps:

[0011] (1) dispersing at least one of natural clay and artificially synthesized layered silicate with a particle size of 10 to 100 nm in water, and forming a colorless transparent sol under the action of at least one mechanical external force selected from the group consisting of high-speed shear emulsification, mechanical stirring, magnetic stirring, and manual stirring;

[0012] (2) at least one of ammonium molybdate, sodium molybdate, molybdenum oxide, phosphomolybdic acid, and ammonium tetrathiomolybdate is used as a molybdenum source, at least one of soluble ammonium tetrathiomolybdate, sodium sulfide, potassium sulfide, ammonium sulfide, thiourea, carbon disulfide thioacetamide, cysteine, and glutathione is used as a sulfur source, and at least one of a reducing sulfur source, hydrazine hydrate, hydroxylamine hydrochloride, oxalic acid, and citric acid is used as a reducing agent and dissolved in water to form a MoS2 precursor solution; the precursor solution has a Mo / S molar ratio of 1:2 to 1:4, and a Mo / reducing agent molar ratio of 1:1 to 1:6.

[0013] (3) The silicate sol obtained in (1) and the MoS2 precursor solution obtained in (2) are mixed under the action of at least one mechanical external force selected from the group consisting of high-speed shear emulsification, mechanical stirring, magnetic stirring, and manual stirring to form a uniform mixed sol; the mass ratio of silicate to MoS2 in the mixed sol is in the range of 0.1 to 10, preferably 0.5 to 2.

[0014] (4) The mixed sol obtained in (3) can be further crystallized at 120-220° C. for 3-72 hours, preferably at 140-180° C. for 24-48 hours. The crystallization method can be a common crystallization method such as heating crystallization in a closed system oven, electric furnace, etc., microwave heating crystallization, open system oil bath heating crystallization, etc.; the product separation in the formed gel can be a product separation method such as polar solvent sedimentation separation, vacuum filtration separation and centrifugal separation. The product is washed with deionized water and ethanol. The product can be dried by vacuum drying, freeze drying, CO2 supercritical drying, natural air drying, etc. to obtain a MoS2 / layered silicate nanocomposite catalyst.

[0015] The MoS2 / layered silicate nanocomposite catalyst prepared by the above method can be used for hydrogenation of at least one heavy oil raw material selected from coal tar, heavy oil, shale oil, catalytic oil slurry, residual oil and extra heavy oil with a suspension phase API of 1 to 20 to produce light oil products. The suspension bed hydrogenation reaction conditions are as follows: the mass percentage of the catalyst is 0.01% to 2.0%, preferably 0.1% to 0.5%; the reaction temperature is 300 to 480°C, preferably 420 to 450°C; the reaction pressure is 10 to 25MPa, preferably 14 to 18MPa.

[0016] The structural characterization analysis of the catalyst prepared by the present invention is as follows: the pure MoS2 sample in the comparative example is 2H-MoS2 with an intercalated structure. The MoS2 / layered silicate nanocomposite catalyst obtained by the present invention is characterized by XRD (X-ray powder diffraction) for its crystal phase structure (see Figure 1 ), the results showed that the obtained nanocomposite catalyst still maintained the crystalline structure of layered silicate, but its stacking degree was significantly reduced, and only a weak MoS2 diffraction peak appeared, indicating that it had a small size and stacking degree. This result shows that MoS2 in the composite catalyst did not aggregate and was small in size; the layered silicate stacking was also broken. HRTEM (high-resolution transmission electron microscopy) was used to characterize the number of stacking layers, layer size and agglomeration of nanosheets of MoS2. HRTEM photos show that the MoS2 in the prepared MoS2 / layered silicate nanocomposite catalyst is a highly dispersed nanosheet with a length of no more than 10nm at the farthest two points of the sheet, a stacking layer number of 1-4 and a thickness of less than 3nm (see Figure 2 ), distributed in islands on the surface of layered silicate, which can greatly expose the active sites of the catalyst. However, the pure MoS2 catalyst is an aggregate of nanosheets, with 4 to 10 layers of stacking layers. The length of the sheet is greater than 10nm, and the exposure of the catalytic hydrogenation active sites is small.

[0017] Compared with the prior art, the present invention has the following advantages and effects:

[0018] (1) The present invention utilizes the regular layered structure characteristics of silicate materials with a layer diameter of 20 to 50 nm and a layer thickness of 0.2 to 1.7 nm, and the characteristics of the silicate material that can be peeled off and highly dispersed into a charged sol in an aqueous solution by mechanical external force, and is compounded with MoS2 which also has a layered structure. The layered silicate sol can form a gel during the static crystallization process, thereby suppressing the increase in the number of MoS2 nanosheet stacking layers and the length of the layer, and suppressing the self-agglomeration of MoS2 nanosheets through the gel environment, so as to achieve the island-like distribution of a single MoS2 nanosheet on the surface of a single silicate disk.

[0019] (2) The characterization results of the catalyst of the present invention show that compared with the control samples of pure MoS2 catalyst, WS2 / layered silicate, and VS2 / layered silicate composite catalyst, the MoS2 / layered silicate nanocomposite catalyst forms an intrinsic layered nanostructure of a single molybdenum sulfide sheet and a single layered silicate disk, and the MoS2 nanosheets in the MoS2 / layered silicate nanocomposite catalyst are small in length, have a small number of stacked layers, and present an island-like highly dispersed composite, which avoids self-agglomeration and can greatly increase the exposure of its catalytic active sites.

[0020] (3) The MoS2 / layered silicate nanocomposite catalyst prepared by the present invention has high dispersibility and exposes abundant catalytic active sites. When used for heavy oil hydrogenation and lightening, its catalytic active sites can fully contact with the reaction substrate, thereby achieving rapid hydrogenation conversion of heavy oil, thereby avoiding the deactivation of catalyst caused by asphaltene coking and precipitation. The reaction results are shown in Table 1. The conversion rate of asphaltene in the heavy oil hydrogenation reaction of the present invention can be as high as 99.5%, the yield of light gasoline and diesel can be as high as 59.5%, and no coking phenomenon occurs, and the heavy oil suspension has a hydrogenation activity far higher than that of the control sample. Description of the drawings:

[0021] Figure 1 XRD patterns of the layered silicate support, the pure MoS2 obtained in Comparative Example 1, and samples with different MoS2 / layered silicate ratios obtained in Examples 1 and 2.

[0022] Figure 2 HRTEM photos of the pure MoS2 obtained in Comparative Example 1 and the sample with a MoS2 / layered silicate ratio of 1 obtained in Example 2. Specific implementation method:

[0023] In order to further illustrate the present invention, embodiments are given below, but they do not limit the scope of the present invention.

[0024] Embodiment 1:

[0025] Weigh 1.0g Laponite (Bick Additives Co., Ltd., USA, artificially synthesized sodium magnesium silicate lithium salt, average particle size 60nm, single layer disc size 25nm, single layer thickness 0.92nm) and disperse it in 60ml deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 0.1104g ammonium heptamolybdate and 0.2556g cysteine ​​and dissolve them in 60ml water under stirring to form a red MoS2 precursor solution. Under 13000r.mp shear emulsification conditions, the above Laponite sol and MoS2 precursor solution are evenly mixed for 10 minutes to obtain a dark red sol. The obtained red sol is transferred to a stainless steel hydrothermal kettle with a polytetrafluoroethylene lining and crystallized at 160°C in an electric furnace for 24 hours. After cooling to room temperature, it is separated by suction filtration and washed with deionized water 3 times to obtain a black solid, which is freeze-dried for 12 hours to obtain a MoS2 / sodium magnesium silicate lithium composite catalyst.

[0026] The test results of the nano-laser particle size analyzer show that the average particle size of the MoS2 / sodium magnesium silicate lithium composite catalyst obtained in this embodiment is 30nm, so MoS2 / sodium magnesium silicate lithium is a nano-composite catalyst. The SEM characterization results of the MoS2 / sodium magnesium silicate lithium nano-composite catalyst show that the MoS2 component in the catalyst is a single nano-sheet of island-like composite on the surface of a single layered sodium magnesium silicate lithium disk with a size of 20 to 30nm. The HRTEM characterization results show that the number of layers of a single MoS2 nano-sheet is 1, the thickness of the sheet is about 1.0nm, and the length of the two farthest points on the side of the sheet is 3-5nm.

[0027] The catalyst prepared in this embodiment is used for the suspended bed hydrogenation lightening reaction of Karamay residue oil with an API of 10, and the amount of catalyst added is 0.15wt.%, and the amount of raw material added is 30g. In the suspended bed hydrogenation reaction, the reaction temperature is 420°C, and the hydrogen reaction pressure is 14MPa. The reaction is carried out for 4h. The main product of the suspended bed hydrogenation of Karamay residue oil is gasoline and diesel, and its yield and asphaltene conversion rate are much higher than those of the catalysts in Comparative Examples 1-3 (see Table 1).

[0028] Embodiment 2:

[0029] Weigh 1.0g Laponite (Bick Additives Co., Ltd., USA, artificially synthesized sodium magnesium silicate lithium salt, average particle size 60nm, single layer disc size 25nm, single layer thickness 0.92nm) and disperse it in 60ml deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 1.1040g ammonium heptamolybdate and 2.5560g cysteine ​​and dissolve them in 60ml water under stirring to form a red MoS2 precursor solution. Under shear emulsification conditions, evenly mix the above Laponite sol and MoS2 precursor solution for 10 minutes to obtain a dark red sol. The obtained red sol is transferred to a polytetrafluoroethylene liner and placed in a microwave synthesizer, and crystallized in an oven at 180°C for 6 hours. After cooling to room temperature, centrifugation is performed, and deionized water is washed 3 times to obtain a black solid, which is vacuum dried for 12 hours to obtain a MoS2 / sodium magnesium silicate lithium composite catalyst.

[0030] The test results of the nano-laser particle size analyzer show that the average particle size of the MoS2 / sodium magnesium silicate lithium composite catalyst obtained in this embodiment is 35nm, so MoS2 / sodium magnesium silicate lithium is a nano-composite catalyst. The SEM characterization results of the MoS2 / sodium magnesium silicate lithium nano-composite catalyst show that the MoS2 component in the catalyst is a single nano-sheet of island-like composite on the surface of a single sodium magnesium silicate lithium disk with a size of about 20 to 30nm. The HRTEM characterization results show that the number of stacked layers of a single MoS2 nanosheet is 2, the thickness of the sheet is about 1.5nm, and the length of the two farthest points on the side of the sheet is 4-6nm.

[0031] The catalyst prepared in this example was used for suspended bed hydrogenation lightening reaction of coal tar with API of 18, the amount of catalyst added was 0.15wt.%, and the amount of raw material added was 30g. In the suspended bed hydrogenation reaction, the reaction temperature was 440°C, the hydrogen reaction pressure was 12MPa, and the reaction was carried out for 4h. The main products of coal tar hydrogenation were gasoline and diesel, and the yield and asphaltene conversion rate were much higher than those of the catalysts in Comparative Examples 1-3 (see Table 1).

[0032] Embodiment 3:

[0033] Weigh 1.0g magnesium silicate (magnesium silicate synthesized by hydrothermal method, with an average particle size of 80nm, a single-layer disc size of 35nm, and a single-layer thickness of 0.95nm measured by a nano-laser particle size analyzer) and disperse it in 60ml of deionized water, and mechanically stir for 1 hour to form a colorless and transparent sol. Weigh 1.6258g ammonium tetrathiomolybdate and 4ml hydrazine hydrate and dissolve them in 60ml water under stirring to form a red MoS2 precursor solution. Under shear emulsification conditions, the above-mentioned magnesium silicate sol and MoS2 precursor solution are uniformly mixed for 10 minutes to obtain a deep red sol. The obtained red sol is transferred to a polytetrafluoroethylene liner and placed in a microwave synthesizer, and crystallized at 180°C for 12 hours. After cooling to room temperature, it is filtered after sedimentation, washed with deionized water 3 times, washed with ethanol 3 times, and a black solid is obtained. After drying naturally for 24 hours, a MoS2 / magnesium silicate composite catalyst is obtained.

[0034] The test results of the nano-laser particle size analyzer show that the average particle size of the MoS2 / magnesium silicate composite catalyst obtained in this embodiment is 40nm, so MoS2 / magnesium silicate is a nano-composite catalyst. The SEM characterization results of the MoS2 / magnesium silicate nano-composite catalyst show that the MoS2 component in the catalyst is a single nano-sheet composited in an island shape on the surface of a single magnesium silicate disk with a size of about 30 to 40nm. The HRTEM characterization results show that the number of layers of a single MoS2 nano-sheet is 2, the thickness of the sheet is about 1.5nm, and the length of the two farthest points on the side of the sheet is 6-8nm.

[0035] The catalyst prepared in this example was used for suspended bed hydrogenation lightening reaction of super heavy oil with API of 5, the amount of catalyst added was 0.15wt.%, and the amount of raw material added was 30g. In the suspended bed hydrogenation reaction, the reaction temperature was 400°C, the hydrogen reaction pressure was 16MPa, and the reaction time was 4h. The main product of the hydrogenation of super heavy oil was gasoline and diesel, and its yield and asphaltene conversion rate were much higher than those of the catalysts in Comparative Examples 1-3 (see Table 1).

[0036] Embodiment 4:

[0037] Weigh 0.5g magnesium silicate (magnesium silicate synthesized by hydrothermal method, with an average particle size of 80nm, a single-layer disc size of 35nm, and a single-layer thickness of 0.95nm measured by a nano-laser particle size analyzer) and disperse it in 30ml deionized water, and stir it magnetically for 1 hour to form a colorless and transparent sol. Weigh 1.6258g ammonium tetrathiomolybdate and 4ml hydrazine hydrate and dissolve them in 90ml water under stirring to form a red MoS2 precursor solution. Under magnetic stirring conditions, the above-mentioned magnesium silicate sol and MoS2 precursor solution are uniformly mixed for 1 hour to obtain a dark red sol. The obtained red sol is transferred to a hydrothermal kettle with a polytetrafluoroethylene liner and crystallized at 200°C in an oven for 16 hours. After cooling to room temperature, centrifugation is performed, and deionized water is washed 3 times to obtain a black solid, which is vacuum dried for 24 hours to obtain a MoS2 / magnesium silicate composite catalyst.

[0038] The test results of the nano-laser particle size analyzer show that the average particle size of the MoS2 / magnesium silicate composite catalyst obtained in this embodiment is 45nm, so MoS2 / magnesium silicate is a nano-composite catalyst. The SEM characterization results of the MoS2 / magnesium silicate nano-composite catalyst show that the MoS2 component in the catalyst is a single nano-sheet composited in an island shape on the surface of a single magnesium silicate disk with a size of about 30 to 40nm. The HRTEM characterization results show that the number of layers of a single MoS2 nano-sheet is 3, the thickness of the sheet is about 2.0nm, and the length of the two farthest points on the side of the sheet is 8-10nm.

[0039] The catalyst prepared in this example was used for the suspended bed hydrogenation lightening reaction of catalytic oil slurry with API of 12, and the amount of catalyst added was 0.15wt.%, and the amount of raw material added was 30g. In the suspended bed hydrogenation reaction, the reaction temperature was 450°C, and the hydrogen reaction pressure was 12MPa for 4h. The main products of the suspended bed hydrogenation of the catalytic oil slurry were gasoline and diesel, and the yield and asphaltene conversion rate were much higher than those of the catalysts in Comparative Examples 1-3 (see Table 1).

[0040] Embodiment 5:

[0041] Weigh 0.1g sodium bentonite (Shanghai Aladdin Biochemical Technology Co., Ltd., natural clay, average particle size 90nm, single layer disc size 50nm, single layer thickness 1.0nm) and disperse it in 30m deionized water, and stir magnetically for 1 hour to form a colorless and transparent sol. Weigh 1.2870g sodium molybdate, 3.8060g thiourea, and 1.3029g hydroxylamine hydrochloride and dissolve in 90ml water under stirring to form a red MoS2 precursor solution. Under magnetic stirring conditions, the above sodium bentonite sol and MoS2 precursor solution are uniformly mixed for 1 hour to obtain a dark red sol. The resulting red sol is transferred to a hydrothermal kettle with a polytetrafluoroethylene liner and crystallized at 200°C in an oven for 16 hours. After cooling to room temperature, direct suction filtration is performed, deionized water is washed 3 times, and a black solid is obtained. After vacuum drying for 24 hours, a MoS2 / sodium bentonite composite catalyst is obtained.

[0042] The test results of the nano-laser particle size analyzer show that the average particle size of the MoS2 / sodium-based bentonite composite catalyst obtained in this embodiment is 75nm, so MoS2 / sodium-based bentonite is a nano-composite catalyst. The SEM characterization results of the MoS2 / sodium-based bentonite nano-composite catalyst show that the MoS2 component in the catalyst is a single nano-sheet of island-like composite on the surface of a single sodium-based bentonite disk with a size of about 45 to 55nm. The HRTEM characterization results show that the number of stacked layers of a single MoS2 nano-sheet is 4, the sheet thickness is about 3.0nm, and the farthest length of the sheet side is 8-10nm.

[0043] The catalyst prepared in this example was used for suspended bed hydrogenation lightening reaction of shale oil with API of 15, and the amount of catalyst added was 0.15wt.%, and the amount of raw material added was 30g. In the suspended bed hydrogenation reaction, the reaction temperature was 480°C, and the hydrogen reaction pressure was 10MPa for 4h. The main products of the suspended bed hydrogenation of shale oil were gasoline and diesel, and the yield and asphaltene conversion rate were much higher than those of the catalysts in Comparative Examples 1-3 (see Table 1).

[0044] Embodiment 6:

[0045] Weigh 0.5g sodium bentonite (Shanghai Aladdin Biochemical Technology Co., Ltd., natural clay, average particle size 90nm, monolayer disc size 50nm, monolayer thickness 1.0nm) and disperse in 30m deionized water, 13000r.mp shear emulsification for 10 minutes to form a colorless transparent sol. Weigh 0.9506g phosphomolybdic acid, 3.8060g thioacetamide, 7.2049g citric acid and stir and dissolve in 90ml water to form a red MoS2 precursor solution. Under shear emulsification conditions, the above-mentioned sodium bentonite sol and MoS2 precursor solution are uniformly mixed for 10 minutes to obtain a dark red sol. The resulting red sol is transferred to a round-bottomed flask with a reflux device and crystallized at 120°C in an oil bath for 60 hours. After cooling to room temperature, suction filtration is performed after sedimentation, and deionized water is washed 3 times to obtain a black solid, and MoS2 / sodium bentonite composite catalyst is obtained after freeze drying for 6 hours.

[0046] The test results of the nano-laser particle size analyzer show that the average particle size of the MoS2 / sodium-based bentonite composite catalyst obtained in this embodiment is 70nm, so MoS2 / sodium-based bentonite is a nano-composite catalyst. The SEM characterization results of the MoS2 / sodium-based bentonite nano-composite catalyst show that the MoS2 component in the catalyst is a single nano-sheet of island-like composite on the surface of a single sodium-based bentonite disk with a size of about 45 to 55nm. The HRTEM characterization results show that the number of stacked layers of a single MoS2 nanosheet is 3, the thickness of the sheet is about 2.5nm, and the length of the two farthest points on the side of the sheet is 6-8nm.

[0047] The catalyst prepared by the present invention is used for the suspended bed hydrogenation lightening reaction of heavy oil with API of 13, the amount of catalyst added is 0.15wt.%, and the amount of raw material added is 30g. In the suspended bed hydrogenation reaction, the reaction temperature is 380°C, the hydrogen reaction pressure is 10MPa, and the reaction is carried out for 4h. The main products of the heavy oil suspended bed hydrogenation are gasoline and diesel, and the yield and asphaltene conversion rate are much higher than those of the catalysts in comparative examples 1-3 (see Table 1).

[0048] Comparative Example 1:

[0049] Weigh 0.1104g of ammonium heptamolybdate and 0.2556g of cysteine ​​and dissolve them in 60ml of water under stirring to form a red MoS2 precursor solution. The resulting red solution was transferred to a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and crystallized at 160°C for 24 hours. After cooling to room temperature, it was separated by suction filtration and washed with deionized water 3 times to obtain a black solid. After freeze drying for 12 hours, a pure MoS2 catalyst was obtained.

[0050] The results of nano-laser particle size test show that the average particle size of pure MoS2 catalyst is 270nm. The SEM characterization results show that the pure MoS2 catalyst obtained in the comparative example is an aggregate of MoS2 nanosheets, and the HRTEM characterization results show that the number of stacked layers of MoS2 nanosheets is 4 to 10, the thickness of the sheet is 3.5-9nm, the length of the farthest two points of the sheet is greater than 15nm, and the exposure of the catalytic hydrogenation active site is small.

[0051] Comparative Example 2:

[0052] Weigh 1.0g Laponite (Bick Additives Co., Ltd., USA, artificially synthesized lithium magnesium silicate, average particle size 60nm, single layer disc size 25nm, single layer thickness 0.92nm) and disperse it in 60ml deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 0.1022g ammonium tungstate and 0.2438g cysteine ​​and dissolve them in 60ml water under stirring to form a red WS2 precursor solution. Under shear emulsification conditions, the above-mentioned sodium magnesium silicate lithium sol and WS2 precursor solution are uniformly mixed for 10 minutes to obtain a dark red sol. The obtained red sol is transferred to a stainless steel hydrothermal kettle with a polytetrafluoroethylene lining and crystallized at 200°C in an electric furnace for 24 hours. After cooling to room temperature, it is separated by suction filtration and washed with deionized water 3 times to obtain a black solid. After freeze drying for 12 hours, a WS2 / sodium magnesium silicate lithium composite catalyst is obtained.

[0053] The test results of the nano-laser particle size analyzer show that the average particle size of the WS2 / sodium magnesium silicate lithium composite catalyst obtained in this embodiment is 45nm, so WS2 / sodium magnesium silicate lithium is a nano-composite catalyst. The SEM characterization results of the WS2 / sodium magnesium silicate lithium nano-composite catalyst show that the length of the two farthest points on the side of the WS2 component layer in the catalyst is 20nm, and the layer area is equivalent to the area of ​​the 20-30nm lithium magnesium silicate disk. The two are parallelly compounded to form a sandwich structure of WS2-lithium magnesium silicate-WS2. The HRTEM characterization results show that the number of WS2 nanosheet stacking layers is 4, the layer thickness is about 4nm, and the length of the two farthest points on the side of the layer is 20nm.

[0054] Comparative Example 3:

[0055] Weigh 1.0g Laponite (Bick Additives Co., Ltd., USA, artificially synthesized sodium magnesium silicate lithium salt, average particle size 60nm, single layer disc size 25nm, single layer thickness 0.92nm) and disperse it in 60ml deionized water. Shear emulsify it for 10 minutes at 13000r.mp to form a colorless and transparent sol. Weigh 0.1016g ammonium metavanadate and 0.2632g L-cysteine ​​and dissolve them in 60ml ethylene glycol under stirring to form a VS2 precursor solution. Under shear emulsification conditions, mix the sodium magnesium silicate lithium sol and VS2 precursor solution evenly for 10 minutes to obtain a sol. The obtained sol is transferred to a stainless steel hydrothermal autoclave with a polytetrafluoroethylene liner and crystallized at 200°C in an electric furnace for 24 hours. After cooling to room temperature, it is separated by suction filtration and washed with deionized water 3 times to obtain a black solid. After freeze drying for 12 hours, a VS2 / sodium magnesium silicate lithium nanocomposite catalyst is obtained.

[0056] The test results of the nano-laser particle size analyzer show that the average particle size of the VS2 / sodium magnesium silicate lithium composite catalyst obtained in this embodiment is 100nm, so VS2 / sodium magnesium silicate is a nano-composite catalyst. The SEM characterization results of the VS2 / sodium magnesium silicate lithium nano-composite catalyst show that the size of the VS2 sheet in the catalyst is 40-60nm, and the size of 20-30nm lithium silicate disks is island-like composite on the surface of the VS2 nanosheet. The HRTEM characterization results show that the number of VS2 nanosheet stacking layers is 6, the sheet thickness is about 4nm, and the length of the two farthest points on the side of the sheet is 40nm.

[0057] The catalyst prepared in Comparative Examples 1-3 was used for the suspension bed hydrogenation lightening reaction of Karamay residue oil with an API of 10, and the amount of catalyst added was 0.15wt.%, and the amount of raw material added was 30g. In the suspension bed hydrogenation reaction, the reaction temperature was 420°C, and the hydrogen reaction pressure was 14MPa for 4h. The main product gasoline and diesel yields and asphaltene conversion rates of the suspension bed hydrogenation of Karamay residue oil are shown in Table 1.

[0058] Table 1 Structure of the MoS2 / layered silicate nanocomposite catalyst prepared by the present invention, heavy oil suspension bed hydrogenation activity and structure and heavy oil suspension bed hydrogenation activity of the comparative catalyst.

[0059]

Claims

1. A MoS2 / layered silicate nanocomposite catalyst, characterized in that: The nanocomposite catalyst comprises MoS2 nanosheets and layered silicate monolayer discs, and is a MoS2 / layered silicate nanocomposite catalyst formed by island-shaped distribution of non-agglomerated MoS2 nanosheets on the surface of the monolayered nanolayered silicate discs. The thickness of the single MoS2 nanosheet is 0.6-3.0 nm, and the distance between the two farthest points on the side of the sheet surface is 1-10 nm; The mass ratio of layered silicate to MoS2 in the composite catalyst is 0.1-10; the diameter of the silicate monolayer disc is 20-50 nm and the thickness is 0.2-1.7 nm; Preparation method of the MoS2 / layered silicate nanocomposite catalyst: (1) Dispersing nano-layered silicate in water to form a colorless and transparent sol under the action of mechanical external force; (2) dissolving a molybdenum source, a sulfur source, and a reducing agent in water to form a MoS2 precursor solution; The molybdenum source is one or a mixture of two or more of ammonium molybdate, sodium molybdate, molybdenum oxide, phosphomolybdic acid, and ammonium tetrathiomolybdate; (3) mixing the silicate sol obtained in step (1) and the MoS2 precursor solution obtained in step (2) under the action of an external mechanical force to form a uniform mixed sol; (4) subjecting the mixed sol obtained in step (3) to crystallization treatment, separating the product in the formed gel, and fully drying to obtain a MoS2 / layered silicate nanocomposite catalyst; The sulfur source used in step (2) is one or a mixture of two or more of soluble ammonium tetrathiomolybdate, sodium sulfide, potassium sulfide, ammonium sulfide, thiourea, carbon disulfide, thioacetamide, cysteine, and glutathione; and the reducing agent used is a reducing sulfur source, one or more of cysteine, glutathione, thioacetamide, and thiourea, and one or more of hydrazine hydrate, hydroxylamine hydrochloride, oxalic acid, and citric acid.

2. The catalyst according to claim 1, characterized in that: The nano-sized layered silicate is one or a mixture of two or more natural clay or artificially synthesized layered silicates with a particle size of 10 to 100 nm.

3. The catalyst according to claim 2, characterized in that: The nano-sized layered silicate is one or more of magnesium silicate, lithium magnesium silicate, and sodium magnesium lithium silicate.

4. The catalyst according to claim 1, characterized in that: The mass concentration of the layered silicate in the mixed sol of step (3) is in the range of 0.8 to 35 mg / ml; the crystallization temperature of the mixed sol of step (4) is in the range of 120 to 220° C., and the crystallization time is in the range of 3 to 72 hours.

5. The catalyst according to claim 4, characterized in that: The crystallization temperature of the mixed sol in step (4) is 140 to 180° C., and the crystallization time is 24 to 48 hours.

6. The catalyst according to claim 1, characterized in that: When a reducing sulfur source is used in step (2), it serves as both a sulfur source and a reducing agent; the molar ratio of Mo to S is 1:2-1:4, the molar ratio of Mo to the reducing agent is 1:1-1:6, and the mass ratio of nano-layered silicate to MoS2 in the mixed sol in step (3) is 0.5-2.

7. The catalyst according to claim 1, characterized in that: The mechanical external force used to form the sol of the layered silicate includes one or more of high-speed shear emulsification, mechanical stirring, magnetic stirring, and manual stirring.

8. An application of the MoS2 / layered silicate nanocomposite catalyst according to claim 1, characterized in that: The MoS2 / layered silicate nanocomposite catalyst can be used for catalytic hydrogenation of heavy oil with an API of 1 to 20 to produce light oil products.

9. The use of the MoS2 / layered silicate nanocomposite catalyst according to claim 8, characterized in that: MoS2 / layered silicate nanocomposite catalyst can be used for suspended liquid phase heavy oil hydrogenation to produce light oil products, wherein the suspended bed hydrogenation reaction conditions are: the heavy oil with API less than 20 is at least one of coal tar, heavy oil, shale oil, catalytic oil slurry, residual oil, and extra heavy oil; the mass percentage of the catalyst is 0.01% to 2.0%; the reaction temperature is 300 to 480°C; and the hydrogen reaction pressure is 10 to 25MPa.

10. The use according to claim 9, characterized in that: The mass percentage of the catalyst is 0.1% to 0.5%; the reaction temperature is 420 to 450° C.; and the hydrogen reaction pressure is 14 to 18 MPa.

Citation Information

Patent Citations

  • Method for complexing hydrothermal synthesis of uniform flower-like MoS2 nanospheres

    CN105417581A

  • A method for preparing molybdenum disulfide microspheres in an inverse microemulsion system

    CN105731542B

  • Preparation method of nano molybdenum disulfide (MoS2) hydrogenation catalyst exposed at high active site

    CN108067257A

  • Preparation method for nano-scale supported molybdenum sulphide catalyst

    CN109465018A